Heart fatty acid-binding protein is associated with phosphorylated tau and longitudinal cognitive changes - Fu, Yan; Wang, Zuo-Teng; Huang, Liang-Yu; Tan, Chen-Chen; Cao, Xi-Peng; Tan, Lan (Frontiers in Aging Neuroscience, 2022)
Background: Perturbation of lipid metabolism is associated with Alzheimer’s disease (AD). Heart fatty acid-binding protein (HFABP) is an adipokine playing an important role in lipid metabolism regulation. Methods: Two datasets separately enrolled 303 and 197 participants. First, we examine the associations of CSF HFABP levels with cognitive measures (including Mini-Mental State Examination, Clinical Dementia Rating sum of boxes, and the cognitive section of Alzheimer’s Disease Assessment Scale) and AD biomarkers (CSF amyloid beta and tau levels). Second, we examine the longitudinal associations of baseline CSF HFABP levels and the variability of HFABP with cognitive measures and AD biomarkers. Structural equation models explored the mediation effects of AD pathologies on cognition. Results: we found a significant relationship between CSF HFABP level and P-tau (dataset 1: β = 2.04, p < 0.001; dataset 2: β = 1.51, p < 0.001). We found significant associations of CSF HFABP with longitudinal cognitive measures (dataset 1: ADAS13, β = 0.09, p = 0.008; CDRSB, β = 0.10, p = 0.003; MMSE, β = -0.15, p < 0.001; dataset 2: ADAS13, β = 0.07, p = 0.004; CDRSB, β = 0.07, p = 0.005; MMSE, β = -0.09, p < 0.001) in longitudinal analysis. The variability of HFABP was associated with CSF P-tau (dataset 2: β = 3.62, p = 0.003). Structural equation modeling indicated that tau pathology mediated the relationship between HFABP and cognition. Conclusions: Our findings demonstrated that HFABP was significantly associated with longitudinal cognitive changes, which might be partially mediated by tau pathology.